x={7/60; 11/60}, x₁+x₂=7/60+11/60=18/60=0,3
Объяснение:
sin5πx-cos5πx=√6/2
(√2/2)(sin5πx-cos5πx)=(√6/2)(√2/2)
sin(π/4)sin5πx-cos(π/4)cos5πx=√3/2
-cos(π/4+5πx)=√3/2
cos(π/4+5πx)=-√3/2
π/4+5πx=±arccos(-√3/2)+2kπ=±(π-arccos(√3/2))+2kπ=±(5π/6)+2kπ, k∈Z
1/4+5x=±5/6+2k
5x=±5/6-1/4+2k
x=±1/6-1/20+0,4k
1) x=1/6-1/20+0,4k=(7+24k)/60
0<(7+24k)/60<0,5
0<7+24k<30
-7/24<k<23/24, k∈Z⇒k=0⇒(7+0)/60=7/60
2) x=-1/6-1/20+0,4k=(-13+24k)/60
0<(-13+24k)/60<0,5
0<-13+24k<30
13/24<k<43/24, k∈Z⇒k=1⇒x=(-13+24)/60=11/60
x₁+x₂=7/60+11/60=18/60=0,3
-9x^2 + 6x - 1 + 10 + 5x - 9 = 0
- 9x^2 + 11x = 0
9x^2 - 11x = 0
x (9x - 11) = 0
x1 = 0
x2 = 1целая 2/9